Perilaku Sosial Anak dari Keluarga Broken home di Kampung Aur, Kelurahan Aur, Kota Medan: (Studi Kasus 5 Anak Keluarga Broken home) - Rimma Putri Masta Napitupulu; Berlianti Berlianti (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2025)
The family is the first environment that shapes a child's personality and social behavior. However, in broken homes, emotional conditions and parenting patterns are often disrupted due to separation or the absence of one parent. This has an impact on the process of shaping children's social behavior in their daily lives. This study aims to analyze the social behavior of children from broken homes in Kampung Aur, Kelurahan Aur, Medan City. A qualitative approach with a case study design was used. The main informants consisted of five children from broken homes who were selected using the snowball technique. Data were collected through observation, in-depth interviews, and documentation, then analyzed using descriptive qualitative methods. The results of the study showed that the children's social behavior had not developed optimally in most indicators, namely cooperation, sharing, competition, empathy, sympathy, imitation, social support, and social acceptance. The main obstacles arise from inconsistent parenting patterns, lack of emotional support, and an unsupportive social environment. Therefore, the active involvement of parents, guardians, and the community is essential to shape and nurture children's social behavior in a sustainable manner.